2015
DOI: 10.1016/j.jenvrad.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Source term estimates of radioxenon released from the BaTek medical isotope production facility using external measured air concentrations

Abstract: BATAN Teknologi (BaTek) operates an isotope production facility in Serpong, Indonesia that supplies (99m)Tc for use in medical procedures. Atmospheric releases of (133)Xe in the production process at BaTek are known to influence the measurements taken at the closest stations of the radionuclide network of the International Monitoring System (IMS). The purpose of the IMS is to detect evidence of nuclear explosions, including atmospheric releases of radionuclides. The major xenon isotopes released from BaTek are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…An in-situ measurement using NaI(Tl) spectrometer performed in the same date by Syarbaini et al reported an increase of the 131 I and 41 Ar concentration level in the air [19]. Furthermore, release of radioxenon ( 133 Xe) was also reported in the study conducted by P. W. Eslinger et al during the operation of the facility [20]. The presence of man-made radionuclide reported by the studies and time-series response of the developed system demonstrate the effectiveness of the monitoring system to capture and quickly detect any short events that are probably related to release of radioactive materials into the atmosphere.…”
Section: Long-term Dose Rate Variationmentioning
confidence: 72%
“…An in-situ measurement using NaI(Tl) spectrometer performed in the same date by Syarbaini et al reported an increase of the 131 I and 41 Ar concentration level in the air [19]. Furthermore, release of radioxenon ( 133 Xe) was also reported in the study conducted by P. W. Eslinger et al during the operation of the facility [20]. The presence of man-made radionuclide reported by the studies and time-series response of the developed system demonstrate the effectiveness of the monitoring system to capture and quickly detect any short events that are probably related to release of radioactive materials into the atmosphere.…”
Section: Long-term Dose Rate Variationmentioning
confidence: 72%